HCV and immigration in Italy - Galli, Massimo; Ridolfo, Annalisa; van denBogaart, Lorena; Negri, Cristina; Giacomelli, Andrea (Acta Biomedica Atenei Parmensis, 2018)
Aim of this survey is to examine the current situation regarding the various migrant populations in Italy, their consistency, their distribution and the known data in terms of prevalence of HCV infection in the countries of origin, possibly distinguishing by age groups, and evaluate the presumed prevalence of HCV infection in the different areas of Italy in relation to the place of departure, in relation to any comparative data already present in Italy. This in order to construct a sort of Italian geographic map - detailed by Regions or by Provinces - of an estimated or predictable number of migrant people, according to the various groups, who carry the HCV infection, in order to provide a summary of information not yet available and which may constitute the starting point for further studies. This is a rather ambitious work because it intends to reason on a composite reality - making it an instrument of dissemination - such as the multifaceted reality of the presence in Italy of migrant populations who arrive or have already arrived from countries of South America, Africa, Eastern Europe of Asia; this in a vision not linked to the current dramatic arrival of immigrants by sea but which falls within a more general context.